2020
DOI: 10.3389/fmicb.2020.596942
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Virulence and Toxin Expression of Vancomycin-Intermediate and Vancomycin-Sensitive Staphylococcus aureus Strains

Abstract: Previous studies on vancomycin-intermediate Staphylococcus aureus (VISA) have mainly focused on drug resistance, the evolution of differences in virulence between VISA and vancomycin-sensitive S. aureus (VSSA) requires further investigation. To address this issue, in this study, we compared the virulence and toxin profiles of pair groups of VISA and VSSA strains, including a series of vancomycin-resistant induced S. aureus strains-SA0534, SA0534-V8, and SA0534-V16. We established a mouse skin infection model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…A previous study by El-sayed et al estimated similar result that VRSA isolates harbored the highest percent of icaA and icaD genes 28 . However, Jin et al reported that VISA isolates had higher biofilm formation capacity encoded by biofilm encoding genes 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by El-sayed et al estimated similar result that VRSA isolates harbored the highest percent of icaA and icaD genes 28 . However, Jin et al reported that VISA isolates had higher biofilm formation capacity encoded by biofilm encoding genes 37 .…”
Section: Discussionmentioning
confidence: 99%
“…For this, we used the Galleria mellonella larvae infection model (Fig. 4g), which has been widely used to study microbial pathogenesis/virulence, including that of S. aureus [27][28][29][30] . Comparative analysis was performed between isolates belonging to groups III (10 out of 27 isolates) and V (13 out of 13 isolates), and a subset of isolates that included S. aureus USA300 and six isolates presenting phenotypes similar to USA300 in vitro, i.e., high replication, and high host cell death (selected from groups IVa, IVb, IVc; Fig.…”
Section: S Aureus Isolates Group Based On Distinctive Intracellular P...mentioning
confidence: 99%
“…Despite the greater therapeutic difficulty in treating VISA infections, VISA appears to be less virulent than VSSA but with a greater ability to colonise and evade the host immune system [ 460 , 461 ]. Prior studies employing a mouse model of skin and soft tissue infection demonstrated that VISA had a much lower invasive capacity than VSSA; VISA also induced lower levels of innate immunity in persistent and chronic infections [ 461 ]. Proposed mechanisms for VISA’s virulence reduction include loss-of-activity mutations or dysfunction of the quorum-sensing, virulence regulator system agr [ 461 ].…”
Section: Vancomycinmentioning
confidence: 99%
“…Prior studies employing a mouse model of skin and soft tissue infection demonstrated that VISA had a much lower invasive capacity than VSSA; VISA also induced lower levels of innate immunity in persistent and chronic infections [ 461 ]. Proposed mechanisms for VISA’s virulence reduction include loss-of-activity mutations or dysfunction of the quorum-sensing, virulence regulator system agr [ 461 ]. Virulence factors under agr control include expression of the α-hemolysin encoded by hla [ 462 ], with mutant or dysfunctional agr VISA isolates found to produce up to 20-fold less α-toxin than VSSA and also less lethal in an in vivo murine bacteraemia model [ 460 ].…”
Section: Vancomycinmentioning
confidence: 99%
See 1 more Smart Citation